2019
DOI: 10.1136/bmjopen-2018-023836
|View full text |Cite
|
Sign up to set email alerts
|

Change of access to emergency care in a repopulated village after the 2011 Fukushima nuclear disaster: a retrospective observational study

Abstract: ObjectivesSustaining emergency care access is of great concern. The aim of this study is to evaluate access to emergency care in a repopulated village following the 2011 Fukushima disaster.DesignThis research was a retrospective observational study. The primary outcome measure was total emergency medical services (EMS) time. A Bayesian time series analysis was performed to consider local time series trend and seasonality.SettingThe residents in Kawauchi Village, Fukushima, Japan were forced to evacuate after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Furthermore, the evacuation order in Odaka Ward affected the Haramachi Ward in the non-evacuated areas (figure 1). Past studies have suggested that EMS response times in evacuated areas may be longer than that in non-evacuated areas after the evacuation order is lifted, [23][24][25][26] and the observed finding is not consistent with these previous studies. 26…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the evacuation order in Odaka Ward affected the Haramachi Ward in the non-evacuated areas (figure 1). Past studies have suggested that EMS response times in evacuated areas may be longer than that in non-evacuated areas after the evacuation order is lifted, [23][24][25][26] and the observed finding is not consistent with these previous studies. 26…”
Section: Discussioncontrasting
confidence: 61%
“…18 23 Additionally, the sociodemographic characteristics of the local population have changed significantly from predisaster levels, as most of the returnees are elderly and reconstruction workers. [23][24][25] This dynamic shift in the evacuation zone, deterioration of the healthcare delivery system and demographic changes may have affected the EMS as well.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…cal resources, and access to healthcare is affected by cost, distance to facilities, and information barriers, in addition to the limited availability of therapists 6,7) . Disaster evacuation and repopulation are known to be complex situations that affect access to various healthcare services, such as emergency medical services 8) . However, there is a lack of information regarding the provision of rehabilitation in limitedresource areas, the distance to the patient's home, the number of staff available, and the frequency of rehabilitation activities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Most of the returning residents are the elderly, making resumption of medical systems in the former evacuation areas a priority. [ 24 , 25 ] Health care systems in the affected areas remain heavily affected since many hospitals in the area were forced to close and remain closed even after the evacuation orders were lifted. [ 23 ] Notably, the situations of emergency transport in the area where the evacuation order was lifted have been shown to be different from those before the disaster, leading to the delay in EMS time.…”
Section: Introductionmentioning
confidence: 99%